Book Review - Charles Fletcher. Muslim-Christian engagement in the twentieth century: the principles of Inter-faith dialogue and the work of Ismail al-Faruqi.(London: I. B. Tauris, 2015.) - Yusuf, Imtiyaz (Islamic Research Institute, Islamabad, Pakistan, 2019)
Charles Fletcher’s Muslim-Christian Engagement in the Twentieth Century comes as a refreshing reminder of the contribution of al-Faruqi to the activity of Muslim-Christian dialogue immediately following the end of colonialism and beginning of the postcolonial era.